A Maçã no Escuro como metáfora da trajetória conceitual da referência no âmbito dos estudos da linguagem - Demétrio, Alana Kercia Barros (2014)
This study addresses the relationship between the drama of language in A maçã no escuro, by Clarice Lispector, and the conceptual trajectory of reference. Leaning on the theoretical contributions which support the transformations involved in this trajectory until the construction of the referenciation concept, we analyzed 43 passages of the novel which we considered associated with the cognition, language and reference triad. Our analysis consisted of examining these passages in light of the philosophical discussion about the truth issue (DAVIDSON, 1974; 2008; MARTINS, 2000; 2004; 2012; RORTY, 1980; WITTGENSTEIN, 1968; 1996); the awakening of Linguistics to the importance of the discursive dimension of referring acts (ARAÚJO, 2004; 2007; BAKHTIN, 1997; BAKHTIN/VOLOSHINOV, 2006; BLIKSTEIN, 2003; CARDOSO, 2003; COSTA, 2007; MONDADA E DUBOIS, 2003) and the construction of the sociocognitive hypothesis as an alternative to the conflict which was raised between essentialism and radical relativism (MARCUSCHI, 2007; SALOMÃO, 1997; 1999; 2005). The results we found indicate the presence of a constant tension in the path taken by the protagonist in the novel, a tension that incorporates, in a certain way, a paradigmatic crisis which is similar to the one that characterizes language studies (MARTINS, 2004); and highlight the character’s assumption, at the end of the narrative, of a conception according to which through language we shape the world, a conception that is therefore analogous to the sociocognitivist vision.